Geomorphology and sedimentology of Porto Pino, SW Sardinia, western Mediterranean. Issue 2 (30th November 2017) - Buosi, Carla; Tecchiato, Sira; Pusceddu, Nicola; Frongia, Paolo; Ibba, Angelo; De Muro, Sandro
ABSTRACT: This paper presents a detailed (1:4000) geomorphological, sedimentological and ecological map of a Mediterranean microtidal wave-dominated beach system and adjacent inner shelf. This map is an innovative cartographic product that integrates a range of processes of present and past timeframes. It is part of a larger cartography on the coastal geomorphology of Sardinia (Italy) aiming to facilitate coastal management practices and future scientific research. The study area is located in SW Sardinia (Italy), and focuses on Porto Pino beach, an important tourist destination of semi-pristine nature, facing environmental pressures common to many coastal Mediterranean settings. In this context, the main human impact on coastal dune habitats is described and a full environmental characterization of the beach system is presented.